Given Lukasiewicz axiom system for Classical Propositional Logic (CPL):

(L1) α→(β→α)

(L2) (α→(β→γ))→(α→β)→(α→γ)

(L3) (¬α→¬β)→(β→α)

and the usual Modus Ponens, does my proof of (P→Q)→((Q→R)→(P→R)) below correct? Can someone point out where I made mistake?

(1) (P→R)→((Q→R)→(P→R)) (L1)

(2) (P→(Q→R))→((P→Q)→(P→R)) (L2)

(3) (Q→R)→(P→(Q→R)) (L1)

(4) (P→Q)→(P→R) (2,3 MP)

(5) (Q→R)→(P→R) (1,4 MP)

(6) (P→Q)→((Q→R)→(P→R)) (4,5 MP)

  • 2
    $\begingroup$ How does your step (4) work? The only deduction I can see from (2), (3) is the derived rule HS giving $(Q\to R)\to((P\to Q)\to(P\to R))$. $\endgroup$ – user10354138 May 22 at 5:27
  • $\begingroup$ You can find the proof in the answer to this post : T2. $\endgroup$ – Mauro ALLEGRANZA May 22 at 6:15

No. Steps 4,5, and 6 are all not correct applications of MP


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.